Towards Transcultural Self-Writing : Mapping the Struggles of Minoritised Cultures in Colombia - Gruber, Valerie; Ndi, Gilbert Shang; Banguero Velasco, Rigoberto (A Relational View on Cultural Complexity : Implications for Theory and Practice, 2023)
More explicitly than in most other countries, the case of Colombia reveals that for members of minoritised groups such as Afrodescendant and indigenous communities, transculturality can be both a mobilising vision of hope and resistance, and a traumatising experience of colonisation and marginalisation. Against this backdrop, our chapter focuses on self-writing as a means of exploring the historical and ethical preconditions for a jointly envisioned transculturality, which are often overlooked in neoliberal discourses of a globalised world. Based on ethnographic experiences and self-writing research from Colombia, we examine how memory, corporality and territoriality constitute avenues of transcultural imagination. We argue that transculturality needs to be rooted in a critical consciousness of historical processes of colonisation, collective trauma and persistently unequal power relations. For peoples of formerly colonised spaces, rewriting the self is a matter of urgency and agency. It is the basis for the (re)negotiation of their existence, interaction and exchange with other cultures.
Keywords: Self-Writing; Transculturality; Afrodescendant; Indigenous; Inequality; Minoritisation; Resistance; Violence; Colonially